Research of rock pressure manifestations in rocks of parting during descending and simultaneous mining of C9 and C10Top coal seams - Kovalevska, I; Symanovych, H; Barabash, M; Snihur, V (National Mining University, 2017)
Purpose. To estimate the probability of interstratal rocks stability loss during simultaneous mining of two seams in series in the descending order. Methods. Methods of a computing experiment and mine observations were used for conducting the research. Findings. Recommendations for the improvement of 914 bolting system parameters of complex roadway for possibility of its reusing are developed. Originality. Regularity of stress-strain state change of parting during simultaneous mining of coal seams with the purpose to reveal the constituent of rock pressure manifestations during the top seam mining is studied. Practical implications. The received results can be generalized for the purpose of providing recommendations concerning bolting and supporting of mine workings during simultaneous mining of seams in series.

Мета. Оцінка ймовірності втрати стійкості порід міжпластя при одночасному відпрацюванні двох пластів у свиті в низхідному порядку. Методика. Для проведення досліджень використовувалися методи обчислювального експерименту та шахтні спостереження. Результати. Розроблено рекомендації щодо вдосконалення параметрів кріпильної системи 914 збірного штреку для забезпечення можливості його повторного використання. Наукова новизна. Вивчено закономірність зміни напружено-деформованого стану міжпластя при одночасному відпрацюванні вугільних пластів з метою виявлення складової проявів гірського тиску при відпрацюванні верхнього пласта. Практична значимість. Отримані результати можуть бути узагальнені з метою видачі рекомендацій щодо кріплення й підтримки виробок при одночасному відпрацюванні пластів у свиті.

Цель. Оценка вероятности потери устойчивости пород междупластья при одновременной отработке двух пластов в свите в нисходящем порядке. Методика. Для проведения исследований использовались методы вычислительного эксперимента и шахтные наблюдения. Результаты. Разработаны рекомендации по совершенствованию параметров крепежной системы 914 сборного штрека для обеспечения возможности его повторного использования. Научная новизна. Изучена закономерность изменения напряженно-деформированного состояния междупластья при одновременной отработке угольных пластов с целью выявления составляющей проявлений горного давления при отработке верхнего пласта. Практическая значимость. Полученные результаты могут быть обобщены с целью выдачи рекомендаций по креплению и поддержанию выработок при одновременной отработке пластов в свите.
Keywords: coal seams; simultaneous mining; stress-strain state; parting; overworking